Resurgence of Large Class Sizes and Pedagogical Reform in 21st Century Secondary School History Classrooms - Godsend T. Chimbi; Loyiso C. Jita (Research in Social Sciences and Technology, 2021)
This paper examines the interaction between class size and teachers’ selection of teaching methods while implementing a new history curriculum in Zimbabwean secondary schools. Policy makers, parents, teachers, and students are worried about large class sizes because they are associated with higher dropout rates, less teacher-student interaction and rote pedagogy. Although class sizes had significantly declined in the latter half of the 20th century, the growth of online learning has witnessed class sizes ballooning in the 21st century, reigniting the class size debate. The large class size challenge has re-emerged in the developed North although the problem has never been resolved in the developing South. Using the theoretical lens of symbolic interactionism and a qualitative multiple case-study approach, data were collected over an eight-week period using document analysis, semi-structured interviews and lesson observations. Results seem to challenge the conventional view that large classes coerce teachers to use rote pedagogy and small classes encourage learner-centric practices. Teachers’ choices of teaching methods were neither linked to class size nor new pedagogical policy. Instead, teachers’ personal philosophy to instruction appeared to be the decisive factor to the teaching methods they used, rather than the size of the class. To promote pedagogical change, improving teacher quality appears a more valuable and cheaper investment than constructing new schools and employing more teachers to reduce class sizes.